If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3 + 4x + -2 = 10x + -20 Reorder the terms: -3 + -2 + 5x + 4x = 10x + -20 Combine like terms: -3 + -2 = -5 -5 + 5x + 4x = 10x + -20 Combine like terms: 5x + 4x = 9x -5 + 9x = 10x + -20 Reorder the terms: -5 + 9x = -20 + 10x Solving -5 + 9x = -20 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -5 + 9x + -10x = -20 + 10x + -10x Combine like terms: 9x + -10x = -1x -5 + -1x = -20 + 10x + -10x Combine like terms: 10x + -10x = 0 -5 + -1x = -20 + 0 -5 + -1x = -20 Add '5' to each side of the equation. -5 + 5 + -1x = -20 + 5 Combine like terms: -5 + 5 = 0 0 + -1x = -20 + 5 -1x = -20 + 5 Combine like terms: -20 + 5 = -15 -1x = -15 Divide each side by '-1'. x = 15 Simplifying x = 15
| 2x*7=14 | | 15=-8r-1-8 | | 3x-x-13+4-6x=12 | | 88888888888/7+6789=x | | 2[15-(2+10)]=x | | -8T+2-3T=-5T-6T | | 100-4(16)= | | 5x+1(3-15)=13x-(1-5) | | 5(5x+3)=25x-8 | | 64x+4=4096 | | 5(29)=5 | | 8c-5(c+2)=7 | | x+3*6=66 | | 9x+15=10x | | 8x+7-4x=23 | | 5(29)+5= | | 8x^3-12x=0 | | 2x^3+17x^2+46x+40= | | 0=n-18-4n | | 20r^2+73r+63=0 | | -0.75p-2=0.25 | | 2x=1.5(x+15) | | 6x^2-42p+60=0 | | 10x+10=10x-2 | | 6x+49=8x-11 | | 3(w+1)+7w=4(w+1)-5 | | 2m+16=4+6m | | 6x+-4+9x+16= | | c^3-9c^2-4c+36=0 | | 2x-5(x-3)=-2+4x-25 | | 4(3z-2)=2(n+1) | | 5(12-2x)=3(7+5x) |